PENGARUH TAX AMNESTY DAN SANKSI PAJAK TERHADAP KEPATUHAN PAJAK (Equilibrium: Jurnal Ekonomi Syariah, 2016)
Increase of tax which is not significantly balanced with the taxpayer increase becomes the tax problem in Indonesia. Tax amnesty program is then held to reform the tax with the goal of increasing tax compliance. This study aimed to determine the effect of tax amnesty on tax compliance of BMT in Karisidenan Pati. This research was field research with quantitative approach. The data were primary and secondary data with survey through questionnaires. There were two independent variables in this study. They were (X1) tax amnesty and (X2) tax penalties. The dependent variable (Y) in this study was tax compliance. The sampling technique used purposive sampling to obtain samples of 55 BMT in Pati, Kudus, and Jepara. The results showed that 1) tax amnesty influences the compliance 0.78 with p value <0:01; 2) tax penalties affect the compliance 0.41 with p value = 0.07.